Eupatorium guiengolense (Asteraceae: Eupatorieae), una nueva especie de Oaxaca, México - Torres-Colín, Leticia; Villaseñor, José Luis (Instituto de Ecología, A.C., 1993)
Collecting efforts in the District of Tehuantepec, Oaxaca, carried out by the National Herbarium, have resulted in the discovery of a new species of Eupatorium. The new species is described and illustrated, and its affinities with E. ovaliflorum are discussed. A key to determine the two species is provided.